Ab initio based kinetic Monte Carlo analysis to unravel the propagation kinetics in vinyl acetate pulsed laser polymerization. Issue 46 (8th November 2017) - Desmet, Gilles B.; Marien, Yoshi W.; Van Steenberge, Paul H. M.; D'hooge, Dagmar R.; Reyniers, Marie-Françoise; Marin, Guy B.
Abstract : The radical propagation kinetics of vinyl acetate in pulsed laser polymerization (PLP) is studied by combining ab initio calculated rate coefficients with kinetic Monte Carlo modeling of PLP spectra. Abstract : The radical propagation kinetics of vinyl acetate (VAc) in pulsed laser polymerization (PLP) is studied by combining ab initio calculated rate coefficients for propagation of head, tail and mid-chain radicals, and backbiting reactions with kinetic Monte Carlo modeling of PLP spectra. The intriguing laser pulse frequency dependency of the propagation kinetics is shown to be mainly caused by the formation of stabilized mid-chain radicals via backbiting of tail radicals, originating from head-to-head propagation. These mid-chain radicals are approximately 35 times less reactive towards propagation at 323 K which, in agreement with experimental observations, results in a 15% increase of the observed propagation rate coefficient if the laser pulse frequency is increased from low (25–100 s −1 ) to high (300–500 s −1 ) values. Under typical PLP conditions, only tail radicals are reactive towards backbiting while this reaction is energetically unfavorable for head radicals. Tail-to-tail propagation of the radicals formed by head-to-head propagation is not sufficiently slow to fully explain the observed frequency dependence. The effect of chain length dependent propagation remains limited but can no longer be neglected at frequencies above 500 s −1 .